PENGEMBANGAN MEDIA PEMBELAJARAN POT SUSUN (STACKED POTS) UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG SISWA - Ulfa, Nanik; Aliyah, Wakhidatul (INCARE, International Journal of Educational Resources, 2023)
This research is motivated by the low numeracy skills of second-grade students at MI Al - Ishlah Kalipare. There are several factors contributing to these numeracy skills, including: 1) students' methods of addition and subtraction and determining the place value of hundreds, tens, and units. 2) Lack of mathematics learning media. To address these issues, the researcher developed a learning media called "pot susun" to improve numeracy skills. The author used the Research and Development (R&D) method, which resulted in a product that can be further developed. The research method employed the ADDIE development model. Data collection techniques included questionnaires, tests, and interviews conducted by the researcher. The research findings indicate that the "pot susun" learning media is suitable for learning, as revisions were made based on feedback from media experts, subject matter experts, and practitioners. The assessment of feasibility and effectiveness showed valid and highly valid results, indicating that this learning media is suitable for improving students' numeracy skills. This is evidenced by a significant improvement in the PreTest and Post Test results, with an increase of 53%. In conclusion, the "pot susun" learning media is highly valid, suitable, and effective in improving numeracy skills for second-grade students at MI Al - Ishlah Kalipare.